A systemic approach to identify relevant information provided by UAV in precision viticulture. (1st June 2017) - Pichon, L.; Besqueut, G.; Tisseyre, B.
Abstract : By providing high spatial resolution images of vine fields througout the vine growing season, UAVs could provide useful information, different than those normally considered in the literature. This study aimed at identifying i) relevant information that can be observed from UAV images by two kind of stakeholders : growers and advisers (G&A) ii) the most suitable periods for this observation iii) and the added value this information can have for both G&A daily tasks. This approach has been conducted on an 11.3 ha commercial vineyard representative of the south of France vineyards. UAV-based visible images (2.5 cm resolution) have been acquired in commercial conditions every two weeks from budburst to harvest. Images have been presented to two groups of G&A six times during the growing season. Every expert gathering was conducted with i) an individual period where images were presented to each expert ii) a collective period where G&As were invited to share information. Application of this methodology demonstrated that much information about the vines, the soil and the vineyard environment can be extracted from UAV-based visible images without any image processing. Results showed that this information have added value all along the growing cycle of the vine, particularly for advisers.